Are socioeconomic inequalities in the incidence of small-for-gestational-age birth narrowing? Findings from a population-based cohort in the South of England. Issue 7 (29th July 2019) - Wilding, Sam; Ziauddeen, Nida; Roderick, Paul; Smith, Dianna; Chase, Debbie; Macklon, Nick; McGrath, Nuala; Hanson, Mark; Alwan, Nisreen A
Abstract : Objectives: To investigate socioeconomic inequalities, using maternal educational attainment, maternal and partner employment status, and lone motherhood indicators, in the risk of small-for-gestational-age (SGA) births, their time trend, potential mediation by maternal smoking and body mass index, and effect modification by parity. Design: Population-based birth cohort using routine antenatal healthcare data. Setting: Babies born at University Hospital Southampton, UK, between 2004 and 2016. Participants: 65 909 singleton live births born to mothers aged ≥18 years between 24-week and 42-week gestation. Main outcome measures: SGA (birth weight <10th percentile for others born at the same number of completed weeks compared with 2013/2014 within England and Wales). Results: Babies born to mothers educated up to secondary school level (adjusted OR (aOR) 1.32, 99% CI 1.19 to 1.47), who were unemployed (aOR 1.27, 99% CI 1.16 to 1.38) or with unemployed partners (aOR 1.27, 99% CI 1.13 to 1.43), were at greater risk of being SGA. There was no statistically significant change in the magnitude of this risk difference by these indicators over time between 2004 and 2016, as estimated by linear interactions with year of birth. Babies born to lone mothers were not at higher risk compared with partnered mothers after adjusting for maternal smoking (aOR 1.05, 99% CI 0.93 to 1.20). The inverse association between maternal educational attainment and SGA risk appeared greater in multiparous (aOR 1.40, 99% CI 1.10 to 1.77) compared with primiparous women (aOR 1.28, 99% CI 1.12 to 1.47), and the reverse was true for maternal and partner's unemployment where the association was stronger in primiparous women. Conclusions: Socioeconomic inequalities in SGA risk by educational attainment and employment status are not narrowing over time, with differences in association strength by parity. The greater SGA risk in lone mothers was potentially explained by maternal smoking. Preventive interventions should target socially disadvantaged women, including preconception and postpartum smoking cessation to reduce SGA risk.